2017
DOI: 10.1016/j.chb.2017.06.042
|View full text |Cite
|
Sign up to set email alerts
|

The interplay between humans, technology and user authentication: A cognitive processing perspective

Abstract: This paper investigates the interplay among human cognitive processing differences (field dependence vs. field independence), alternative interaction device types (desktop vs. touch) and user authentication schemes (textual vs. graphical) towards task completion efficiency and effectiveness. A four-month user study (N=164) was performed under the light of the field dependence-independence theory which underpins human cognitive differences in visual perceptiveness as well as differences in handling contextual i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 56 publications
1
23
0
Order By: Relevance
“…Their research revealed that users with individual differences in cognitive processing styles (i.e., verbals vs. imagers, field-dependent vs. field-independent) perform significantly different during login with alphanumeric and graphical passwords. Imagers outperformed Verbals (Belk et al, 2013a) and field-independent individuals outperformed field-dependent individuals (Belk et al, 2017a) in login tasks when using a recognition-based GUA scheme. Katsini et al (2018b) revealed that field-independent individuals created stronger passwords when using a recall-based GUA scheme than field-dependent individuals.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…Their research revealed that users with individual differences in cognitive processing styles (i.e., verbals vs. imagers, field-dependent vs. field-independent) perform significantly different during login with alphanumeric and graphical passwords. Imagers outperformed Verbals (Belk et al, 2013a) and field-independent individuals outperformed field-dependent individuals (Belk et al, 2017a) in login tasks when using a recognition-based GUA scheme. Katsini et al (2018b) revealed that field-independent individuals created stronger passwords when using a recall-based GUA scheme than field-dependent individuals.…”
Section: Related Workmentioning
confidence: 99%
“…Regarding elementary cognitive processing abilities, Belk et al (2013b) reported that users with enhanced working memory and cognitive processing speed outperformed users with more limited processing abilities during textual and graphical login tasks. Belk et al (2017a) investigated the effects of cognitive processing styles towards users' login performance and memorability of alphanumeric and graphical passwords.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…The work in [156] offered an overview on how to make the passwords memorable while keeping them relatively usable and secure at the same time. Paper by Belk et al [157] delivered a research on the task completion efficiency and effectiveness among the conventional passwords and the realistic ones. The results revealed that, for most of the participants, the utilization of graphic passwords requires more time than for the textual ones.…”
Section: Usabilitymentioning
confidence: 99%